2019
DOI: 10.5056/jnm19136
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Dysmotility in Murine Partial Colonic Obstruction Due to Functional Changes in Interstitial Cells

Abstract: Background/Aims Interstitial cells play important roles in gastrointestinal (GI) neuro-smooth muscle transmission. The underlying mechanisms of colonic dysmotility have not been well illustrated. We established a partial colon obstruction (PCO) mouse model to investigate the changes of interstitial cells and the correlation with colonic motility. Methods Western blot technique was employed to observe the protein expressions of Kit, platelet-derived growth factor receptor-α (Pdgfra), Ca 2+-activated Cl-(Ano1) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…As shown in Figure 2B, application of NPPB (5-Nitro-2-[3-phenylpropylamino] benzoic acid, 10 µM) inhibited slow wave, which is consistent to the study. 4 As shown in Figure 2C, the application of apamin (1 µM) did not affect the slow wave frequency illustrating that ICC are without SK3 channel, consistent with other studies. 5,6 Note, the slow wave amplitude shown is above the half of average, thus not counted as change.…”
Section: To the Editorsupporting
confidence: 89%
See 3 more Smart Citations
“…As shown in Figure 2B, application of NPPB (5-Nitro-2-[3-phenylpropylamino] benzoic acid, 10 µM) inhibited slow wave, which is consistent to the study. 4 As shown in Figure 2C, the application of apamin (1 µM) did not affect the slow wave frequency illustrating that ICC are without SK3 channel, consistent with other studies. 5,6 Note, the slow wave amplitude shown is above the half of average, thus not counted as change.…”
Section: To the Editorsupporting
confidence: 89%
“…Secondly, electrophysiological measurements have shown that a specific antagonist of SK chan-nels on CMMCs which cannot be accounted for the targeting on PDGFRα + cells since SMCs and neurons are also enriched with SK3. We provide here an example as shown in Figure 2 to illustrate isolated slow wave which may support the study of Wang et al 4 Slow wave activity was recorded in normal mice under the similar conditions as described by Wang et al, 4 except for the presence of tetrodotoxin (TTX) 1 µM (neuronal activity blocker) and nifedipine 1 µM (L-type calcium channel blocker inhibiting muscular activity). This is the classic activity for slow waves reflecting ICC unique activity.…”
Section: To the Editorsupporting
confidence: 80%
See 2 more Smart Citations
“…The dilated sections showed muscle hypertrophy but normal responses to cholinergic stimulation, whereas the transition zone with luminal narrowing showed a marked reduction in response to cholinergic stimulation with loss of ganglia and variable levels of ICC network reduction (218). In a murine model of partial obstruction and proximal dilation, ICC were reduced and PDGFR-a þ cells upregulated, correlated with a decrease in the generation of colonic motor complexes (219). ICC loss in the hypertrophic muscle in the dilated segment was correlated with loss of stem cell factor and an increase in TNF-a (220).…”
Section: Chronic Idiopathic Pseudo-obstructionmentioning
confidence: 98%